2012
DOI: 10.3109/15412555.2012.630701
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Importance of a Reduced FEV1/FEV6

Abstract: The FEV(1)/FEV(6) is not as sensitive as the FEV(1)/FVC for diagnosing airways obstruction, but in the presence of a normal FEV(1)/FVC, subjects have greater physiologic abnormalities than when only the FEV(1)/FVC is reduced. The FEV(1)/FEV(6) ratio should not replace the FEV(1)/FVC as the standard for airways obstruction, but there is benefit including this measurement to identify individuals with greater air trapping and diffusion abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Patients with FEV 1 /FEV 6 < 0.73 but FEV 1 /FVC above 0.70 or LLN had greater air trapping and airway wall thickness, poorer functional capacity, and a greater number of respiratory exacerbations at follow-up in comparison to those with reduced FEV 1 /FVC in isolation [82]. Similar results have been demonstrated in other large cohorts [52,83]. FEV 1 /FEV 6 was found to be less sensitive than FEV 1 /FVC to detect obstruction, but those with isolated reduction in FEV 1 /FEV 6 had greater physiologic abnormalities in spirometry, diffusing capacity, and metrics of air trapping [83].…”
Section: Time-fractioned Lung Volume Indicessupporting
confidence: 79%
“…Patients with FEV 1 /FEV 6 < 0.73 but FEV 1 /FVC above 0.70 or LLN had greater air trapping and airway wall thickness, poorer functional capacity, and a greater number of respiratory exacerbations at follow-up in comparison to those with reduced FEV 1 /FVC in isolation [82]. Similar results have been demonstrated in other large cohorts [52,83]. FEV 1 /FEV 6 was found to be less sensitive than FEV 1 /FVC to detect obstruction, but those with isolated reduction in FEV 1 /FEV 6 had greater physiologic abnormalities in spirometry, diffusing capacity, and metrics of air trapping [83].…”
Section: Time-fractioned Lung Volume Indicessupporting
confidence: 79%
“…None of these studies compared the relationship between each spirometric measure and other assessments of disease because the researchers assumed that FEV 1 / FVC was the reference standard for diagnosis of airflow obstruction. In contrast, Morris and colleagues, in a large, retrospective study of prebronchodilator spirometric tests, found that subjects who were positive by FEV 1 /FEV 6 criteria alone had more hyperinflation and air trapping and lower inspiratory capacity and diffusion capacity of carbon monoxide than subjects with reduced FEV 1 /FVC alone (26).…”
Section: Original Researchmentioning
confidence: 91%
“…Subjects with significant air trapping might reach and exceed their equal pressure point earlier and more peripherally before complete emptying and hence have FVC lower than expected for their age, creating a falsely high FEV 1 /FVC, a phenomenon that should be less likely to occur if FEV 6 is used. Thus, Morris et al [ 28 ] describe that the FEV 1 /FEV 6 ratio better identifies early anomalies in lung volumes or in diffusing capacity than FEV1/FVC, which is especially important since hyperinflation [ 29 ] as well as reduced diffusing capacity [ 30 ] are independent predictors of mortality in COPD.…”
Section: Discussionmentioning
confidence: 99%